Evaluating Methodologies: A Procedure and Application to Nuclear Power Plant Siting Methodologies - Ford, Coleen K.; Keeney, Ralph L.; Kirkwood, Craig W. (Management Science, 1979)
A procedure is presented to evaluate the appropriateness of alternative methodologies for analyzing a specified problem. This procedure is illustrated by identifying desirable characteristics of nuclear power plant site selection methodologies and evaluating the adequacy of methodologies that have been used to select nuclear power plant sites. Objectives of such siting methodologies are specified and attributes developed to measure the degree of attainment of each objective. Several siting methodologies are rated on the various attributes and these ratings are analyzed to determine the adequacy of each methodology.